Natural resource conservation : management for a sustainable future - Chiras, Daniel D., ....-; Reganold, John P., ....- (Upper Saddle River : Pearson, 2005)
For introductory-level, undergraduate courses in natural resource conservation, natural resource management, environmental science, and environmental conservation.This comprehensive text provides the ecological principles, policies, and practices to manage a sustainable future. It emphasizes practical, cost-effective, sustainable solutions to these problems that make sense from social, economic, and environmental perspectives.
Keywords: Sustainability ; environment